Influence of group work on development of educational motivation of pupils at physics lessons - Kudusov, A.S.; Akhmetova, Т.B.; Konyrbaуeva, A.K. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
Article is devoted to a group form of work at physics lessons as, working in groups, pupils profit from communication and cooperation with different people. At the same time, during group work at physics lessons for the purpose of increase of cognitive interest of pupils’ application of various approaches is traced. So, for example strategy of critical thinking assumes work in groups, strategy of dialogue training confirms that children effectively study at their active involvement in discussions and discussions. It should be noted that at group form of education pupils develop both in social and in the emotional plan that is have opportunity to communicate with contemporaries, to protect and represent the ideas, to exchange opinions, to take active part in mutually estimation and estimation themselves.
Физика сабақтарында оқушылардың оқу ынтасын қалыптастыруға бағытталған топтық жұмыстың əсері
Влияние групповой работы на формирование учебной мотивации учащихся на уроках физики
Keywords: Motivation; physics lessons; group work; educational; pupils